Matrine Alleviates Oxidative Stress and Inflammation in Colon Cancer by Activating the Nrf2 Pathway - Dong, Yun-Fei; Shang, Tao (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Oxidative stress (OS) and inflammation are pivotal for colon cancer (CC) development, which can be regulated by the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway. Matrine (MAT) can treat disorders by modulating OS and inflammation with the Nrf2 pathway. This study aimed to investigate the effects of MAT in CC. Materials and Methods: Mice pretreated with MAT were injected with 1,2-dimethylhydrazine (DMH) to induce CC. Then, colon tissue pathology was examined, and B cell lymphoma-2 (Bcl-2), Bcl-2 associated X (Bax) and antigen identified by monoclonal antibody Ki 67 (Ki-67) expressions in colon tissues were quantified. Moreover, HT-29 cells were treated with MAT and transfected with si-Nrf2 to further investigate the mechanisms of MAT on CC. Following treatment with MAT, the viability and apoptosis of HT-29 cells were detected. Furthermore, OS- and inflammation-related factors, as well as Nrf2 pathway-related expressions, were measured both in vivo and in vitro. Results: Matrine treatment alleviated DMH-induced epithelial structural changes, increased Bcl2 and Ki-67 expressions, but decreased Bax expression in the colon. In vitro, MAT inhibited viability but induced apoptosis in HT-29 cells. Both in vivo and in vitro results revealed that MAT alleviated OS and inflammation, increased Nrf2, NAD(P)H quinone dehydrogenase 1, and heme oxygenase-1 expressions, but reduced kelch-like ECH-associated protein 1 expression in CC models. However, the effects of MAT on CC were reversed by Nrf2 knockdown. Conclusion: Matrine may alleviate OS and inflammation in CC by activating the Nrf2 pathway, suggesting that MAT may be a promising strategy in CC treatment. Cite this article as: Dong Y, Shang T. Matrine Alleviates Oxidative Stress and Inflammation in Colon Cancer by Activating the Nrf2 Pathway. Turk J Gastroenterol. 2025;36(9):563-572.